Greek Views of Music - Strunk, Oliver 1901-1980; Mathiesen, Thomas J. (New York Norton, 1998)
This collection presents three entire treaties, as well as excerpted writings on music by Plato, Aristotle, and others. Included is the first English translation of Gaudentius's complete Harmonic Introduction, prepared by the volume's editor, Thomas J. Mathieson, who also revised the other translations in light of recent scholarship. These selections not only illuminate Greek thinking about music, they also help us understand ideas about music set forth by medieval and Renaissance writers and theorists.
Keywords: Classical Antiquity (8th Century BC-6th Century AD); Music history; Greece